Evaluation of stress among dental undergraduates and postgraduates using salivary cortisol as a biomarker - V Vasanthi; Rooban Thavarajah; Elizabeth Joshua; Umadevi K Rao; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2022)
Background: Stress is a non-specific response of the body to any demand. Professional education has a certain level of stress inherent in it. Dental students have been reported in the literature to experience more stress than medical students. Objective: To evaluate the stress levels of dental students: first-year undergraduates, house surgeons, and final-year postgraduates, using salivary cortisol as a stress biomarker. Materials and Methods: Dental students above 18 years of age and without any systemic illness were included in the study. Those students with a drug history of corticosteroids, anti-depressants, and oral contraceptives were excluded from the study. Female participants experiencing pre-menstrual symptoms, pregnancy, and familial stressor issues were excluded from the study. First-year undergraduates, house surgeons, and final-year postgraduates were enrolled in the study. Unstimulated whole saliva was collected in the morning and evening between 9:00 and 10:00 am and between 3:00 and 4:00 pm. Salivary cortisol levels were assessed by chemiluminescence immuno-assay (CLIA). Results: Paired sample t-test was used to compare the diurnal variation among morning and afternoon samples within the groups. The salivary cortisol levels were found to be significant within the groups. One-way ANOVA was used to compare the salivary cortisol levels between the groups. The salivary cortisol levels within the groups were not statistically significant. Conclusion: Salivary cortisol is a non-invasive biomarker of stress. Postgraduates had higher salivary cortisol levels than other study groups.